DYNAMIC METHOD FOR MANAGEMENT OF INVESTMENT FINANCIAL RESOURCES IN AGRICULTURE - M. Dimitrova (Trakia Journal of Sciences)
Farm management is related to the decisions that affect the profitability of this business. Limited resources are allocated, and after taking a certain risk, a return is expected. In order to manage risk effectively, it needs to be clearly identified and valued. Determining the production structure of an agricultural holding in the current study is considered in the short term, in the case of choosing between two annual crops. Solving this problem in the future involves establishing the amount of investment funds, areas in which to invest, and the use of tangible fixed assets as efficiently as possible. In carrying out the investment process, financial and investment decisions are made, developing this dynamic method for every possible alternative to investing capital. The purpose of this study is to propose a method for making management decisions in agriculture, when choosing to invest financial resources in terms of choosing between two crops - wheat and sunflower.